KETERAMPILAN KEPEMIMPINAN SITUASIONAL KIAI (Studi Analisis di Pondok Pesantren Bustanul Falah Banyuwangi) - Wahyono, Imam; Fanani, Ahmad Aziz (Tarbiyatuna Kajian Pendidikan Islam, 2022)
In the midst of individualist nature and materialistic lifestyles that are increasingly thickening, islamic boarding schools are still consistent with presenting an educational system that is able to bridge the physical (physical) and mental spiritual (spiritual) needs of humans. The uniqueness of the role of pesantren is certainly inseparable from the professionalism and intelligence of the kyai in leading the pesantren education community. It was at this point that the main reason for the study was raised. The main focus in the discussion is Situational Leadership Skills Kiai which focuses on skills in terms of diagnosis, flexible leadership style and partnering towards success. It is a qualitative research with its type of approach that has a phenomenological pattern. Data collection techniques with observations, interviews, documents and audiovisual materials. Data analysis techniques with condensation data, display data and conclusion drawing/verifiying. The results of this study include Kiai's skills in diagnosing by providing potential tests to the pesantren community which aims to determine their abilities and commitment. Flexible skills in various leadership styles depend on the competence and commitment of the pesantren community. Meanwhile, the skill of partnering towards success is characterized by building communication and building teamwork.